Quantification of Beat-To-Beat Variability of Action Potential Durations in Langendorff-Perfused Mouse Hearts - Tse, Gary; Du, Yimei; Hao, Guoliang; Li, Ka Hou Christien; Chan, Fiona Yin Wah; Liu, Tong; Li, Guangping; Bazoukis, George; Letsas, Konstantinos P.; Wu, William K. K.; Cheng, Shuk Han; Wong, Wing Tak (Frontiers in Physiology, 2018)
Background: Beat-to-beat variability in action potential duration (APD) is an intrinsic property of cardiac tissue and is altered in pro-arrhythmic states. However, it has never been examined in mice. Methods: Left atrial or ventricular monophasic action potentials (MAPs) were recorded from Langendorff-perfused mouse hearts during regular 8 Hz pacing. Time-domain, frequency-domain and non-linear analyses were used to quantify APD variability. Results: Mean atrial APD (90% repolarization) was 23.5±6.3 ms and standard deviation (SD) was 0.9±0.5 ms (n=6 hearts). Coefficient of variation (CoV) was 4.0±1.9% and root mean square (RMS) of successive differences in APDs was 0.3±0.2 ms. The peaks for low- and high-frequency were 0.7±0.5 and 2.7±0.9 Hz, respectively, with percentage powers of 39.0±20.5 and 59.3±22.9%. Poincaré plots of APDn+1 against APDn revealed ellipsoid shapes. The ratio of the SD along the line-of-identity (SD2) to the SD perpendicular to the line-of-identity (SD1) was 8.28±4.78. Approximate and sample entropy were 0.57±0.12 and 0.57±0.15, respectively. Detrended fluctuation analysis revealed short- and long-term fluctuation slopes of 1.80±0.15 and 0.85±0.29, respectively. When compared to atrial APDs, ventricular APDs were longer (ANOVA, P<0.05), showed lower mean SD and CoV but similar RMS of successive differences in APDs and showed lower SD2 (P<0.05). No difference in the remaining parameters was observed. Conclusion: Beat-to-beat variability in APD is observed in mouse hearts during regular pacing. Atrial MAPs showed greater degree of variability than ventricular MAPs. Non-linear techniques offer further insights on short-term and long-term variability and signal complexity.